Arabidopsis AGDP1 links H3K9me2 to DNA methylation in heterochromatin - Cuijun Zhang; Xuan Du; Kai Tang; Zhenlin Yang; Li Pan; Peipei Zhu; Jinyan Luo; Yuwei Jiang; Hui Zhang; Huafang Wan; Xingang Wang; Fengkai Wu; et al. (Nature Communications, 2018)
DNA methylation and H3K9 dimethylation are two linked epigenetic marks of silenced chromatin in plants that depend on the activity of CMT3/2 and SUVH4/5/6. Here the authors identify AGDP1 as an H3K9me2-binding protein required for heterochromatic non-CG DNA methylation, H3K9 dimethylation, and transcriptional silencing.